Hydroboration of Alkenes Catalysed by a Nickel N‐Heterocyclic Carbene Complex: Reaction and Mechanistic Aspects. Issue 41 (8th July 2020) - Ulm, Franck; Cornaton, Yann; Djukic, Jean‐Pierre; Chetcuti, Michael J.; Ritleng, Vincent
Abstract: The pentamethylcyclopentadienyl N‐heterocyclic carbene nickel complex [Ni(η 5 ‐C5 Me5 )Cl(IMes)] (IMes=1, 3‐dimesitylimidazol‐2‐ylidene) efficiently catalyses the anti‐Markovnikov hydroboration of alkenes with catecholborane in the presence of a catalytic amount of potassium tert ‐butoxide, and joins the very exclusive club of nickel catalysts for this important transformation. Interestingly, the regioselectivity can be reversed in some cases by using pinacolborane instead of catecholborane. Mechanistic investigations involving control experiments, 1 H and 11 B NMR spectroscopy, cyclic voltammetry, piezometric measurements and DFT calculations suggest an initial reduction of the Ni II precursor to a Ni I active species with the concomitant release of H2 . The crucial role of the alkoxo‐catecholato‐borohydride species resulting from the reaction of potassium tert ‐butoxide with catecholborane in the formation of an intermediate nickel‐hydride species that would then be reduced to the Ni I active species, is highlighted. Abstract : Top cat : Initial reduction of the air‐stable Ni II precursor [NiCp*Cl(IMes)] to the [Ni I Cp*(IMes)] active species provides an efficient catalyst for the regioselective hydroboration of alkenes.